The optimization of network model of marketing research - Івченко, Н.Б.; Целих, С.О. (Eastern-European Journal of Enterprise Technologies, 2010)
The construction of network diagram of marketing researches is examined, the early and late terms of performing of events a matrix method are calculated, a critical way and his length is determined. Iteration procedure of diminishing of length of critical way is offered due to the redistribution of labour resources.